Predictive Models for the Effect of Storage Temperature on Vibrio parahaemolyticus Viability and Counts of Total Viable Bacteria in Pacific Oysters (Crassostrea gigas) - Fernandez-Piquer, Judith (American Society for Microbiology, 2011)
Vibrio parahaemolyticus is an indigenous bacterium of marine environments. It accumulates in oysters and may reach levels that cause human illness when postharvest temperatures are not properly controlled and oysters are consumed raw or undercooked. Predictive models were produced by injecting Pacific oysters (Crassostrea gigas) with a cocktail of V. parahaemolyticus strains, measuring viability rates at storage temperatures from 3.6 to 30.4°C, and fitting the data to a model to obtain parameter estimates. The models were evaluated with Pacific and Sydney Rock oysters (Saccostrea glomerata) containing natural populations of V. parahaemolyticus. V. parahaemolyticus viability was measured by direct plating samples on thiosulfate-citrate-bile salts-sucrose (TCBS) agar for injected oysters and by most probable number (MPN)-PCR for oysters containing natural populations. In parallel, total viable bacterial counts (TVC) were measured by direct plating on marine agar. Growth/inactivation rates for V. parahaemolyticus were −0.006, −0.004, −0.005, −0.003, 0.030, 0.075, 0.095, and 0.282 log(10) CFU/h at 3.6, 6.2, 9.6, 12.6, 18.4, 20.0, 25.7, and 30.4°C, respectively. The growth rates for TVC were 0.015, 0.023, 0.016, 0.048, 0.055, 0.071, 0.133, and 0.135 log(10) CFU/h at 3.6, 6.2, 9.3, 14.9, 18.4, 20.0, 25.7, and 30.4°C, respectively. Square root and Arrhenius-type secondary models were generated for V. parahaemolyticus growth and inactivation kinetic data, respectively. A square root model was produced for TVC growth. Evaluation studies showed that predictive growth for V. parahaemolyticus and TVC were “fail safe.” The models can assist oyster companies and regulators in implementing management strategies to minimize V. parahaemolyticus risk and enhancing product quality in supply chains.